Immunochemical analysis of cartilage proteoglycans. Radioimmunoassay of the molecules and the substructures. - Wieslander, J (1980)
Antibodies specifically reacting with the link proteins, the hyaluronic acid-binding region and chondroitin sulphate-peptides were used to design specific radioimmunoassay procedures. The sensitivity of the method used for the link protein was about 20 ng/ml, and the other two components could be determined at concentrations of about 2 ng/ml. The radioimmunoassay procedures were tested by using proteoglycan subfractions or fragments thereof. The procedures used to quantify link protein and hyaluronic acid-binding region showed no cross-interference. Fragments of trypsin-digested proteoglycan monomers still reacted in the radioimmunoassay for hyaluronic acid-binding region. Subfractions of proteoglycan monomers separated according to size had a gradually higher relative content of the hyaluronic acid-binding region compared with both chondroitin sulphate-peptides and uronic acid, when the molecules were smaller. The proteoglycans therefore may contain a variably large chondroitin sulphate-rich region, which has a constant substitution with polysaccharide side chains.